2013
DOI: 10.1093/icesjms/fst147
|View full text |Cite
|
Sign up to set email alerts
|

Are Calanus spp. shifting poleward in the North Atlantic? A habitat modelling approach

Abstract: Chust, G., Castellani, C., Licandro, P., Ibaibarriaga, L., Sagarminaga, Y., and Irigoien, X. 2014. Are Calanus spp. shifting poleward in the North Atlantic? A habitat modelling approach. – ICES Journal of Marine Science, 71: 241–253. In the last decade, the analysis based on Continuous Plankton Recorder survey in the eastern North Atlantic Ocean detected one of the most striking examples of marine poleward migration related to sea warming. The main objective of this study is to verify the poleward shift of zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 61 publications
7
78
0
Order By: Relevance
“…These attributes make them a key group for monitoring the impacts of climate change on biodiversity and ecosystem functioning (Richardson, 2008). So far, SDMs have seldom been applied to study plankton biogeography, with only a handful of studies on phytoplankton (Irwin et al, 2012;Pinkernell and Beszteri, 2014;Brun et al, 2015;Rivero-Calle et al, 2015;Barton et al, 2016) and some more on zooplankton (e.g., Reygondeau and Beaugrand, 2011;Chust et al, 2014b;Villarino et al, 2015;Brun et al, 2016;Benedetti et al, in press). This is due not only to the limited data availability for model development, but also due to several unaddressed methodological issues.…”
Section: Species Distribution Modeling-running Before We Can Walk?mentioning
confidence: 99%
See 1 more Smart Citation
“…These attributes make them a key group for monitoring the impacts of climate change on biodiversity and ecosystem functioning (Richardson, 2008). So far, SDMs have seldom been applied to study plankton biogeography, with only a handful of studies on phytoplankton (Irwin et al, 2012;Pinkernell and Beszteri, 2014;Brun et al, 2015;Rivero-Calle et al, 2015;Barton et al, 2016) and some more on zooplankton (e.g., Reygondeau and Beaugrand, 2011;Chust et al, 2014b;Villarino et al, 2015;Brun et al, 2016;Benedetti et al, in press). This is due not only to the limited data availability for model development, but also due to several unaddressed methodological issues.…”
Section: Species Distribution Modeling-running Before We Can Walk?mentioning
confidence: 99%
“…Moreover, disentangling the effects of anthropogenic climate change on plankton distribution and phenology shifts from other drivers (e.g., climate variability, population dynamics) is equally challenging (Chust et al, 2014b). In particular, the combination of controlling factors, together with systematic biases in sampling effort can lead to biases in estimated trends.…”
Section: Adrift In An Ocean Of Changementioning
confidence: 99%
“…Ongoing climate change, particularly seawater warming, is affecting and will continue to affect predominant copepods of the genus Calanus, resulting in distributional changes with consequences for higher trophic levels Chust et al, 2014;Olsen et al, 2011;Reygondeau and Beaugrand, 2011a). While a previous study has already revealed differences in the thermal stress response between closely related Calanus species , the degree of variation in responses of different Calanus populations is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The highest population densities of C. finmarchicus are found along the south-west to north-east axis of the North Atlantic where temperatures range between 4°C and 9°C (Planque and Batten, 2000;Sundby, 2000). Since the 1960s a consistent northward shift of C. finmarchicus distribution has been detected (Beaugrand et al, 2002;Chust et al, 2014). In the North Sea this decrease in the abundance of C. finmarchicus has been associated with an increase of the more southern species C. helgolandicus, which has a lower lipid content and different phenology than C. finmarchicus Bonnet et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation